The effect of air pollution on children's health: A comparative study between La Plata and Bahía Blanca, Buenos Aires province, Argentina - Colman Lerner, Jorge Esteban (2014)
We present the results of a study of outdoor air quality in two comparable regions of Buenos Aires province (Argentina); La Plata and Bahía Blanca, developed jointly by researchers of the National University in both cities, and of the Hospital of Bahía Blanca, between 2009 and 2011. Both regions are characterized by a large petrochemical complex and a village with outstanding traffic. In this study, we measure levels of volatile organic compounds (VOCs), particulate matter suspended in air (PM) in air outdoor and affectation of respiratory system in children between 6 and 12 years. Also, analysis of the effect of the air pollution exposure was made through the calculation of potentially increased life time cancer risk (LCR) in children. In both regions, including three areas: urban, industrial and residential (reference area), 20 VOCs were sampled by passive monitoring (3M 3500), and determined by GC/FID, comprising n-alkanes, cycloalkanes, aromatics, chlorinated compounds, terpenoids and ketones; particulate matter (PM10) was token using a low flow sampler MiniVol TAS, and spirometry were performed, using a portable spirometer. The collected data show higher levels of PM10 in Bahía Blanca, both in the industrial zone and urban areas, the industrial area of Bahía Blanca with very bad air quality, associable with a 5% increase in mortality. The levels of total VOCs found in the residential area for both regions are comparable. Spirometry parameters of children living in an industrial area evidence respiratory disease with respect to urban and residential areas.